Oil and Biodiesel Production from Mortierella isabellina Biomass by a Direct Near-Critical Fluid Extraction and Transesterification Method - Daniela Sallet; Gustavo Andrade Ugalde; Marcus Vinícius Tres; Marcio Antonio Mazutti; Giovani Leone Zabot; Raquel Cristine Kuhn (Biomass)
Oil and biodiesel produced from lipidic microorganisms are gaining attention in the scientific area. However, intracellular oil needs additional steps for its recovery for transesterification, which generally uses catalysts. In this context, thermal processes that do not use catalysts demand to be investigated. Therefore, the objective was to produce oil and biodiesel from Mortierella isabellina biomass by direct transformation of dry microbial biomass without using a catalyst. Near-critical fluid extraction (nCFE) of lipids followed by direct transesterification was carried out with the same equipment, as an intensification process. A central composite design was used to evaluate the influence of temperature, pressure, and solvent mass-to-feed mass ratio on the extraction yield. Microbial lipids produced by submerged fermentation and extracted by nCFE with ethanol were used for biodiesel production. The highest total extraction yield (55.4 wt%) and biodiesel conversion (22.2%) were obtained at 300 °C and 20 MPa with 30 g of ethanol/g of fungal biomass. The other conditions yielded extraction yields and biodiesel conversions ranging from 9.7 to 46.0% and from 1.5 to 22.0%, respectively. The interaction between temperature and pressure was significant (p < 0.05), with a positive correlation, indicating that higher temperatures and pressures yielded higher biodiesel conversion rates. The process intensification is advantageous because it is developed sequentially in one step and uses only ethanol as a solvent/reagent, without catalysts. Therefore, the direct extraction and transesterification of Mortierella isabellina lipids demonstrated to be technically feasible and an environmentally friendly technology for the production of fungal oil and biodiesel. The oil can be used in the food and cosmetic industries because it has nutrients that regulate physiological mechanisms promoting human health, while biodiesel can be used in the transport sector and in stationary engines.